If it's not what You are looking for type in the equation solver your own equation and let us solve it.
9(5x-8)+4=-9(6-6x)
We move all terms to the left:
9(5x-8)+4-(-9(6-6x))=0
We add all the numbers together, and all the variables
9(5x-8)-(-9(-6x+6))+4=0
We multiply parentheses
45x-(-9(-6x+6))-72+4=0
We calculate terms in parentheses: -(-9(-6x+6)), so:We add all the numbers together, and all the variables
-9(-6x+6)
We multiply parentheses
54x-54
Back to the equation:
-(54x-54)
45x-(54x-54)-68=0
We get rid of parentheses
45x-54x+54-68=0
We add all the numbers together, and all the variables
-9x-14=0
We move all terms containing x to the left, all other terms to the right
-9x=14
x=14/-9
x=-1+5/9
| t/5-3=2 | | m/2+13=17 | | -7(4K-6)=-36-2k | | X+2x-16=90 | | 21/x=6 | | 6+6p=-7(4+4p) | | m/9-71=-64 | | 1.4y=16.8 | | y=1/5-4 | | 2x+2-3x+5=3+5 | | 7u+18=81 | | 2=s4-1 | | 3/4x-1=-11 | | 12+7a+3+5=-2a-7 | | 23-5n=7-8(1+n) | | 7(x-7.8)=9.8 | | -19-6=x | | 54+2x-4=90 | | 6(w-93)=18 | | 2x2+6x=40 | | 6/z-9=7 | | 2842=29(x+35) | | 5(3n+1)=2(6n+7) | | x^1/3=-1/3 | | 2=14-2k | | (-4)(5)=x | | n/2+13=17 | | -1.01=w+5.3 | | 20=4+2y | | 8+5r+5+12=r+5 | | 7+3(x–4)–10=-45 | | x+-x=1 |